BS EN 61951-2 AMD1. Secondary cells and batteries containing alkaline or other non acid electrolytes. Secondary sealed cells and batteries for portable applications. Part 2. Nickel-metal hydride (18th June 2021) - British Standards Institution,
No abstract available